The role of the value system in building the ethical behavior of human resources: دراسة تحليلية لأراء عينة من الموظفين في جامعات العتبة الحسينيــة - علاء فرحان طالب; Al-Hasnawi, زينب سالم (Iraqi Journal for Administrative Sciences, 2024)
The aim of the study is to know the role of the value system building the ethical behavior of human resources according to a group of employee opinions in educational institutions in the Holy Karbala governorate. The value system was measured based on the model (Stanley & Waldrop, 1952), which consisted of six dimensions Theoretical values, economic values, aesthetic values social values, political values, religious values) and moral behavior was measured according to the model: (Nishimura & Yamada, 2021) consisting of three dimensions (autonomy / independence, justice, charity / non-abuse). The tool that was used in collecting data and information from the members of the representatives of the sample was (the questionnaire), and (200) questionnaires were distributed to the universities (Wareth Al-Anbiya University, Al-Zahra University.